Dunia tanpa Islam: Pergulatan Wacana Seputar Agama sebagai Sumber Konflik di Indonesia - Muhammad Fakhruddin Al-Razi; Imam Amrusi Jailani (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2024)
Although there is a lot of legitimacy that says no religion teaches hostility, in reality, conflict often colors religious life. The number of conflicts that arose and were related to religion has finally brought academic discourse to a struggle among thinkers related to the discourse of religion as a source of conflict. This article highlights the conflicts in Indonesia due to the discourse of thinkers. The article explores several related literature to illustrate how the discourse is debated. Some Qur'anic verses and their interpretations are also included to emphasize the author's argument and positioning in the discourse. At the national level, domestic thinkers are divided into two camps between those who say religion is a source of conflict and those who do not. At the international level, this discourse even reaches the assumption of religion, especially Islam, as a threat. Some Western thinkers have also proposed the idea of a world without Islam or even without religion. This article concludes that religious conflicts contain many complex elements so that religion cannot necessarily be used as a scapegoat for all problems. Moreover, the behavior of religious people will determine the face of religion in society, so improving religious behavior is the key rather than thinking of eliminating religion itself.